2016
DOI: 10.1007/s00268-016-3652-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Predicting Occult Lymph Node Metastasis in Patients with Clinical Stage I Non‐small Cell Lung Cancer Staged by Integrated Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography

Abstract: The SUV of the primary tumour, adenocarcinoma and tumour size were risk factors for occult lymph node metastasis in patients with NSCLC diagnosed as clinical stage I by preoperative integrated FDG-PET/CT. These findings would be helpful in selecting candidates for mediastinoscopy or endobronchial ultrasound-guided transbronchial needle aspiration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 28 publications
2
41
0
Order By: Relevance
“…There are several techniques for lymph node dissection, including preoperative integrated fluorodeoxyglucose positron emission tomography/CT and freezing sections of lymph nodes during surgery; however, it is much more feasible and practical for surgeons to make a decision using preoperative clinicopathological characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…There are several techniques for lymph node dissection, including preoperative integrated fluorodeoxyglucose positron emission tomography/CT and freezing sections of lymph nodes during surgery; however, it is much more feasible and practical for surgeons to make a decision using preoperative clinicopathological characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…In non‐small cell lung cancer (NSCLC), quantitative measures of PET tracer uptake – (so called‐Maximum Standardised Uptake Value (SUV max )) has been shown to be able to predict occult nodal metastases from the metabolic activity of the primary tumour . In a multivariate analysis SUV max was independent of tumour size and importantly type of tumour, for predicting the presence of occult lymph node metastasis . In an initial study of 63 patients, an Optimal cut‐off value of 8.8 SUV max of the primary tumour was shown to predict occult metastases in NSCLC although in another larger cohort ( n = 163), an SUV max of 7 was deemed to be the best threshold for indicating metastatic risk; a value <7 was shown to be an independent prognostic factor for metastasis‐free survival .…”
Section: Metastatic Risk Assessmentmentioning
confidence: 99%
“…Then, studies with <100 patients were excluded to secure study quality. As shown in Table , seven reports have documented the usefulness of primary tumor SUVmax for the risk stratification of mediastinal ONM using a variety of cut‐off values . Li et al showed that tumor size and primary tumor SUVmax were independently associated with mediastinal ONM in patients with clinical stage I NSCLC .…”
Section: Introductionmentioning
confidence: 99%
“…Li et al showed that tumor size and primary tumor SUVmax were independently associated with mediastinal ONM in patients with clinical stage I NSCLC . More recently, Kaseda documented that classification of NSCLC specifically as ADC is one of the risk factors of ONM; this is in addition to primary tumor size and SUVmax . When examining ONM, some studies did not include FDG PET/CT parameters, but described other predictive risk factors, such as tumor size, ADC histology, and female sex .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation